Penerapan Konsep Green Chemistry dalam Mitigasi Dampak Pencemaran Laut pada Ekosistem Pesisir Aceh - Mazwan Mazwan; Evi Mauliza; Minarni Minarni; Agustizar Agustizar; Jhon Wahidi (Universitas Pendidikan Ganesha, 2026)
The coastal Aceh area of is facing serious marine pollution, primarily caused by human activities such as tourism, fishing, and the improper disposal of household waste and plastic. This situation disrupts the ecological balance and degrades the environmental quality of the coastal ecosystem. This study aims to evaluate the extent of marine pollution and explore the potential application of green chemistry principles as a sustainable mitigation strategy. A mixed-methods approach was used, combining field observations, interviews with local residents and tourism stakeholders, and laboratory analysis of water and sediment samples collected from three coastal sites Ujong Batee in Aceh Besar Regency. The findings reveal a significant decline in seawater quality, indicated by high levels of Biochemical Oxygen Demand (BOD) and heavy metals such as lead and mercury, which exceed acceptable environmental limits. The main contributing factors are inadequate waste management and low environmental awareness. In conclusion, green chemistry offers a promising solution through eco-friendly technologies and community involvement, supported by effective policies and continuous environmental education.